A decadal analysis of bioeroding sponge cover on the inshore Great Barrier Reef - Blake D. Ramsby (Nature Portfolio, 2017)
Abstract Decreasing coral cover on the Great Barrier Reef (GBR) may provide opportunities for rapid growth and expansion of other taxa. The bioeroding sponges Cliona spp. are strong competitors for space and may take advantage of coral bleaching, damage, and mortality. Benthic surveys of the inshore GBR (2005–2014) revealed that the percent cover of the most abundant bioeroding sponge species, Cliona orientalis, has not increased. However, considerable variation in C. orientalis cover, and change in cover over time, was evident between survey locations. We assessed whether biotic or environmental characteristics were associated with variation in C. orientalis distribution and abundance. The proportion of fine particles in the sediments was negatively associated with the presence-absence and the percent cover of C. orientalis, indicating that the sponge requires exposed habitat. The cover of corals and other sponges explained little variation in C. orientalis cover or distribution. The fastest increases in C. orientalis cover coincided with the lowest macroalgal cover and chlorophyll a concentration, highlighting the importance of macroalgal competition and local environmental conditions for this bioeroding sponge. Given the observed distribution and habitat preferences of C. orientalis, bioeroding sponges likely represent site-specific – rather than regional – threats to corals and reef accretion.